IMPROVING STUDENTS’ READING COMPREHENSION THROUGH JIGSAW TECHNIQUE - Halimah Halimah; Helpiana Purba; Cynantia Rachmijati (IKIP Siliwangi, 2019)
The purpose of this research is to investigate of using jigsaw technique to improve reading comprehension at the tenth grade students in SMAN 1 Ngamprah. The total number of sample in this study was 60 students in two classes. It used pre-experimental design that applies in the treatments to measure the significant scores pre-test and post-test. Pre-test was applied in the first meeting. Whereas post-test was applied after the treatments given. After given pre-test and post-test, the researcher got the mean scores in both of the class. There are 57.00 and 80.17 in experimental class and the control class are respectively 57.00 and 79.17. The result show that using jigsaw technique had the positive effect in improving reading comprehension because there was a significant post- test scores of students in two classes with the level significance 0.05. The significance in post-test is 0.355 it was higher than 0.05. It concluded that students’ response toward the implementation of jigsaw technique is effective because they are enjoyed and interested in the learning process. Moreover, the jigsaw technique could help them to improve their reading comprehension.